3D-printed simulator for nasopharyngeal swab collection for COVID-19 - Sananès, Nicolas (Eur Arch Otorhinolaryngol, 2020)
INTRODUCTION: Testing for COVID-19 is a cornerstone of pandemic control. If conducted inappropriately, nasopharyngeal swab collection can be painful and preanalytical sample collection errors may lead to false negative results. Our objective was to develop a realistic and easily available synthetic simulator for nasopharyngeal swab collection. MATERIALS AND METHODS: The nasopharyngeal swab collection simulator was designed through different development steps: segmentation, computer-aided design (CAD), and 3D printing. The model was 3D printed using PolyJet technology, which allows multi-material printing using hard and soft materials. RESULTS: The simulator splits in the parasagittal plane close to the septum to allow better visualization and understanding of nasal cavity landmarks. The model is able to simulate the softness and texture of different structural elements. The simulator allows the user to conduct realistic nasopharyngeal swab collection. A colored pad on the posterior wall of the nasopharynx provides real-time feedback to the user. The simulator also permits incorrect swab insertion, which is of obvious benefit from a training perspective. Comprehensive 3D files for printing and full instructions for manufacturing the simulator is freely available online via an open access link. CONCLUSION: In the context of the COVID-19 pandemic, we developed a nasopharyngeal swab collection simulator which can be produced by 3D printing via an open access link, which offers complete operating instructions.